Teacher performance in carrying out duties as curriculum developers in schools - Lukman Lukman; Nurhayati Nurhayati (Inovasi Kurikulum, 2024)
The research aims to determine the competency and performance of Mataram City MTsN 1 teachers in planning, implementing, and evaluating the Merdeka curriculum. The research method used is qualitative. The research location is MTs Mataram City, Mataram City State. The data collection techniques used were observation, interviews, and documentation studies. The research results concluded that teachers' performance in carrying out their duties as curriculum developers generally showed performance in their role as educators. Factors that support teacher performance in carrying out their responsibilities as curriculum developers are the quality of the principal's leadership, teacher educational background, teacher welfare level, school environment, and facilities and infrastructure. Efforts are being made to improve teacher performance, namely empowering teacher development platforms, such as MGMP, providing opportunities for teachers to take part in higher education at state universities and private universities, as well as through various training activities, upgrading, workshops, seminars, improving teacher welfare, the role of supervisors, completing the facilities and infrastructure needed by teachers in carrying out teaching and learning process activities. Recommendations from the results of this research are addressed to school principals, teachers, and future researchers.   Abstrak Tujuan penelitian untuk mengetahui kompetensi dan kinerja guru MTsN 1 Kota Mataram dalam merencanakan, melaksanakan, dan mengevaluasi kurikulum Merdeka. Metode penelitian yang digunakan adalah metode kualitatif. Lokasi penelitian di MTs Kota Mataram Negeri Kota Mataram. Teknik pengumpulan data yang digunakan dalam penelitian adalah dengan observasi, wawancara, dan studi dokumentasi. Hasil penelitian disimpulkan bahwa kinerja guru dalam melaksanakan tugas sebagai pengembang kurikulum secara umum sudah memperlihatkan kinerja yang sesuai dengan perannya selaku pendidik. Faktor-faktor yang mendukung kinerja guru dalam melaksanakan tugas sebagai pengembang kurikulum adalah kualitas kepemimpinan kepala sekolah, latar belakang pendidikan guru, tingkat kesejahteraan guru, lingkungan sekolah, dan sarana dan prasarana. Upaya-upaya yang dilakukan untuk meningkatkan kinerja guru yaitu memberdayakan wadah-wadah pembinaan guru, seperti MGMP, memberi kesempatan kepada guru untuk mengikuti pendidikan yang lebih tinggi di Perguruan Tinggi Negeri dan di Perguruan Tinggi Swasta, maupun melalui berbagai kegiatan pelatihan, penataran, lokakarya, seminar, peningkatan kesejahteraan guru, peran pengawas, melengkapi sarana dan prasarana yang dibutuhkan oleh guru dalam melaksanakan kegiatan proses belajar mengajar. Rekomendasi dari hasil penelitian ini ditujukan kepada, kepala sekolah, guru, serta peneliti selanjutnya. Kata Kunci: Kinerja guru; pengembang kurikulum; pengembangan kurikulum; sekolah